Learning and the reform of Chinese foreign policy - Dittmer, Lowell 1942-2024 (East Asian Institute (EAI) contemporary China series, 1999)
This volume looks at China's foreign policy from the perspective of learning theory, a relatively new approach to foreign policy analysis based on social psychology. It begins by attempting to conceptualize China's distinctive approach to policy learning, and then proceeds with a tentative periodization of China's learning experience from 1979 to 1999. It concludes that Chinese foreign policy learning has exhibited a certain continuity since the founding of the People's Republic, with learning and teaching structured to alternate with and complement each other